(untitled) (Південний архів (історичні науки), 2026)
This study focuses on regimental and company-level accounting and statistical records as an essential component of the system of official communication within the Hetmanate during the second half of the seventeenth and the eighteenth centuries. The primary aim of the research is to determine their functional purpose, informational capacity, and role in maintaining administrative interaction between the governing institutions of the Cossack state. A detailed examination of this group of documents makes it possible to identify specific features of their formal structure and to highlight the mechanisms of information exchange between interdependent branches of authority in the Hetmanate period. Methods. The research is based on a combination of general scholarly and specialized methods, including historical-typological, structural-functional, comparative, and source-critical analysis. The application of document studies methodology allowed for the clarification of the internal structure of document forms, their content organization, and the communicative functions performed by accounting and statistical records produced by regimental and company chanceries. Results. It has been established that accounting and statistical documents – such as registers, lists, computational records, oath and record books, census books, and revisions – served not only statistical and fiscal purposes but also fulfilled an important communicative function by facilitating information flows between different levels of authority. Their significance for the personalization of Cossack company units and for the reconstruction of the social structure of the population has been analyzed. The study demonstrates that these documents constitute a unique source base that enables the tracing of transformations in administrative practices under the influence of the imperial policies of the Russian state. Conclusions. Regimental and company-level accounting and statistical documents represent a valuable source for the study of official communication, administrative traditions, and the socio-economic development of the Hetmanate. Owing to their multifunctional nature, these texts inform, regulate, identify, and contribute to the formation of historical memory. Their analysis provides deeper insight into the functioning of the Ukrainian administrative system and its transformation under colonial Russian influence, particularly given that the subsequent development of record-keeping practices in Ukraine occurred within the framework of their unification with the administrative standards of the Russian Empire.